Healthcare Quality in the Czech Republic within the European Union Context - M. Říha; E. Lenčová; Z. Broukal (Czech Dental Chamber, 2013)
Introduction, Aim: Current health systems of the European Union Member States are characterized by free movement of patients and health professionals and international transfer of medical and information technologies. The issue of assuring the quality of medical services provided to the European Union nationals outside their home member state is therefore critical. The aim of the short communication is to introduce the readers to parameters for healthcare quality evaluation in healthcare facilities in the European Union and to analyze the current situation in the Czech Republic and measures needed. Discussion: Currently the healthcare quality definition focuses not only on patients, but also on healthy individuals and general population. The healthcare quality evaluation covers not only treatment and rehabilitation, but also on health support and prevention of diseases. The healthcare quality is regulated at several levels by market mechanisms, self-regulation and different regulatory measures. The purpose of medical quality management is to improve clinical and organizational structures and processes. The healthcare quality evaluation is standardized and focuses on pre-defined parameters of healthcare inputs, processes and outputs. One of the standard tools for improving the healthcare quality is clinical audit. Its purpose is an evaluation of clinical procedures in order to implement the necessary measures to increase the quality of clinical practice and patient safety. The above tools can be used in all medical branches and all types of healthcare facilities, from individual general practitioners to clinics and hospitals. Conclusions: A number of measures to improve the healthcare quality, both regulatory and voluntary, have been implemented in the Czech Republic. An important task for the near future is to systematically introduce clinical standards in all medical branches including dental medical facilities. It is also necessary to improve the area of informing patients and involving them into the prevention and treatment process.